Residual Pesticide in the Liver of Rats after Poisoning with Galaxifop-R-Methyl Pesticide Check - Mirkhamidova Parida, Parpieva Mashkhura, Tuychieva Dilfuza (International Journal of Modern Agriculture, 2021)
Galaxyphop-R-methylgerbicide is administered once a day in a laboratory aqueous solution of white rats by probe method LD50 1/10 dose, and on the 5th, 10th, 20th, 30th, 40th, 50th days after poisoning, the residual pesticides in the liver of rats was determined using the APCI (Atmospheric pressure chemical ionization) method. According to the results, the highest concentration of residual pesticide was detected on day 5 after rat poisoning and was 0.0174 mkg / g. The High performance liquid chromatograph mass spectrum - HPLC MS (6420) Tripl Quad LC / MS (Agilent Ttchnologies, USA) was used for analysis.